2015
DOI: 10.3945/ajcn.114.104380
|View full text |Cite
|
Sign up to set email alerts
|

Higher nutritional quality at no additional cost among low-income households: insights from food purchases of “positive deviants”

Abstract: In this low-income population, actual diet cost was positively correlated with nutritional quality, yet the results showed that higher diet quality is not necessarily more costly when foods with higher nutritional quality for their price are selected. The Opticourses intervention was registered at clinicaltrials.gov as NCT02383875.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 41 publications
4
45
0
1
Order By: Relevance
“…Previous studies from the UK ( 4 , 8 , 9 ) , Spain ( 3 , 10 ) , France ( 6 , 11 , 12 ) , the Netherlands ( 13 ) and the USA ( 5 , 14 18 ) all suggest that healthier diets cost more. Typically, higher-quality diets are characterised by higher intakes of whole grains, lean meats, fruits and vegetables, and by lower intakes of fats and sugars, and refined grains ( 19 , 20 ) .…”
mentioning
confidence: 99%
“…Previous studies from the UK ( 4 , 8 , 9 ) , Spain ( 3 , 10 ) , France ( 6 , 11 , 12 ) , the Netherlands ( 13 ) and the USA ( 5 , 14 18 ) all suggest that healthier diets cost more. Typically, higher-quality diets are characterised by higher intakes of whole grains, lean meats, fruits and vegetables, and by lower intakes of fats and sugars, and refined grains ( 19 , 20 ) .…”
mentioning
confidence: 99%
“…More recently, a minimal allotment of 7.50 US$ per week was proposed by An and colleagues as suitable to entail an evolution of the purchasing behaviour [22]. Besides, a study performed in France among a similar population showed that about 20% of the households (called "positive deviants") developed strategies allowing them to purchase healthier food than others, without increasing their food budget [63].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a number of papers that argue (using price per gram or per serving) you can eat healthily on a limited budget (17,18) . Using the cost of the diet, some observational studies found that certain population groups can achieve higher-quality diets at a lower cost than other groups (19,20) . Others report that if foods are carefully selected it is possible to consume a low-cost diet relatively low in energy density and high in nutrient density (21)(22)(23) but this requires a motivated and knowledgeable shopper (18) .…”
Section: Price Metricsmentioning
confidence: 99%